Superficial Inferior Epigastric Artery Flap: Vascular Pattern and Territory Across the Midline - Lohasammakul, Suphalerk; Tonaree, Warangkana; Suppasilp, Chaiyawat; Numwong, Terasut; Ratanalekha, Rosarin; Han, Hyun Ho (Journal of Reconstructive Microsurgery, 2023)
Background Superficial inferior epigastric artery (SIEA) flap offers a significant advantage of lower donor site morbidity over other abdominal-based flaps for breast reconstruction. However, the inconsistent anatomy and territory across the midline remains a major issue. This study aimed to investigate the SIEA and determine its pattern and territory across the midline.Methods Twenty cadavers were studied. Ipsilateral dye was injected to the dominant SIEA. Dissection was performed to evaluate the SIEA origin, artery and vein pattern, vessel diameter, and dye diffusion territory.Results Overall, three SIEA patterns were identified: bilateral presence (45%), ipsilateral presence (30%), and bilateral absence (25%). The territory depended on the vessel course and dominant SIEA diameter, not on its common origin from the femoral artery, at the pubic tubercle level. Regarding the midline territory (pubic tubercle level to umbilicus), SIEA (type 1a) with a diameter of ≥1.4 mm on either side supplied at least half the distance, whereas SIEA with a diameter of <1 mm was limited to the suprapubic area.Conclusion Designing a SIEA flap island across the midline is feasible when contralateral SIEA is present to augment the contralateral territory (e.g., type 1a SIEA) or in SIEA with a common/superficial external pudendal artery origin. Preoperative imaging studies are important for confirming the SIEA system. When the diameter at the origin of the SIEA flap is larger than 1.4 mm, the blood supply to the ipsilateral and contralateral sides is sufficient to enable safe flap elevation.
Keywords: breast reconstruction; autologous; free flap; SIEA flap; across midline